SOMMATORY OF CHILLING HOURS AND CHILLING UNITS AT DIFFERENT REGIONS OF PARANÁ STATE - Botelho, Renato Vasconcelos; Ayub, Ricardo Antonio; Müller, Marcelo Marques Lopes (Scientia Agraria, 2006)
THe actual agro-climate zones for temperate fruit trees at Paraná State, Brazil, is too much generalized, disabling an accurate recommendation of species and cultivars for each region. Thus, this study aimed to estimate the accumulated chilling units in different regions of Paraná, in order to obtain a safer indication for fruit producers. From historical data since 2000 to 2004, collected on meteorological stations at Palmas, Guarapuava, Ponta Grossa and Curitiba; it was calculated the number of chilling hours with temperatures lower or equal to 7,2o C, as well as its estimative by Angelocci Model. Additionally, it was determined the number of chilling units by estimates means of four different methods: Utah Model, Modified Utah Model, North Caroline Model and Modified North Caroline Model. Analyzing the average chilling hours ( 7,2º C), accumulated from May to September, it was verified that the regions presented distinct temperature regimes. Palmas showed the higher average (402.4 h), followed by Guarapuava (308.6 h), Ponta Grossa (169.2 h) and Curitiba (161.8 h). On the same way, the estimates of chilling units by other models also showed differences between regions, confirming the need of distinct planting recommendations of temperate fruit trees in Paraná State.